Parametric analysis on drilling of aluminium alloy hybrid composites reinforced with SIC/WC. (1st June 2022) - Babu, S Senthil; Dhanasekaran, C; Anbuchezhiyan, G; Palani, Kumaran
Abstract: Aluminium alloy (Al7075) based hybrid metal matrix composites reinforced with Silicon carbide (SiC) and Tungsten carbide (WC), at 5 wt% each are considered for this investigation, which are developed by stir casting methodology. Material characteristic analysis both at micro and macro (Tensile strength and micro hardness) level were performed. This investigation is further progressed with drilling of the composites using titanium aluminium nitride coated carbide drill (5mm diameter) for varied point angle, feed rate and drill speed. The responses such as thrust force, surface roughness and roundness error were investigated by adopting Response Surface Methodology (RSM). Multiple linear regression (MLR) is developed along with Artificial Neural Networks (ANN) model for predicting the outputs. Scanning Electron Microscope (SEM) image reveals the uniform distribution of ceramic particles in matrix which ascertains enhanced mechanical properties. The parameters such as feed rate and point angle are found to have significant influence during drilling process. The roundness error is found higher with higher point angle which is due to the wider cutting edges in the drill bit. For unconstrained multi-objective optimization, the optimal condition obtained are 128°- point angle, 0.05 mm rev −1 feed rate and 1000 rpm drill speed. For constrained optimization (roundness error ≤0.05 mm), optimal conditions are 118° point angle, 0.05 mm rev −1 feed rate and 1000 rpm drill speed.